Mosaic Trisomy 7 at Amniocentesis: Prenatal Diagnosis and Molecular Genetic Analyses - Chih-Ping Chen; Yi-Ning Su; Schu-Rern Chern; Yuh-Ming Hwu; Shuan-Pei Lin; Chyong-Hsin Hsu; Fuu-Jen Tsai; Tao-Yeuan Wang; Pei-Chen Wu; Chen-Chi Lee; Yu-Ting Chen; Li-Feng Chen; et al. (Elsevier, 2010)
Objective: To present prenatal diagnosis and molecular genetic analyses of mosaic trisomy 7. Materials, Methods and Results: A 38-year-old primigravid woman underwent amniocentesis at 19 weeks of gestation because of her advanced maternal age. Amniocentesis revealed a karyotype of 47,XY,+7[26]/46, XY[16]. Repeated amniocentesis at 21 weeks of gestation revealed a karyotype of 47,XY,+7[20]/46,XY[17]. Simultaneous cordocentesis revealed a karyotype of 46,XY in 100/100 cultured lymphocytes. Polymorphic DNA marker analyses of uncultured amniocytes and cord blood revealed a diallelic pattern with seemingly equal biparental inheritance of chromosome 7. Repeated cordocentesis and chorionic villus sampling at 23 weeks of gestation revealed a karyotype of 47,XY,+7[2]/46,XY[66] in cord blood and a karyotype of 47,XY,+7 in 24/24 cultured chorionic villi cells. Level II ultrasonography was normal. At 40 weeks of gestation, a 2,708 g normal male baby was delivered. The peripheral blood had a karyotype of 46,XY in 100/100 lymphocytes. Molecular analyses of placenta, urine, buccal swab, and peripheral blood revealed a diallelic pattern and seemingly equal biparental inheritance of chromosome 7 in all tissues. At 3 months of age, he manifested hypopigmented skin and inguinal hernia, but showed normal growth and mental development. Fluorescence in situ hybridization analysis of inguinal hernia sac tissue revealed that 19/100 (19%) of nuclei had three chromosome 7 signals. Conclusion: Mosaic trisomy 7 at amniocentesis may be derived from a cell culture artifact from an undetected low level of trisomy 7 mosaicism in uncultured amniocytes, and can be associated with favorable fetal outcome if the blood has a normal karyotype or a very low level of mosaicism and if uniparental disomy for chromosome 7 is excluded.